Religiusitas dan Kesejahteraan Subjektif pada Pasien Jantung Koroner - Firma Agus Tina; Muhana Sofiati Utami (Gadjah Mada Journal of Psychology (GamaJoP), 2016)
This research aimed to examine the relationship between religiousity andsubjective well being among coronary heart patients in X hospital. It was hypothesizedthat there is a positive relationship between religiousity and subjective well being. Therewere 67 coronary heart patients in this research between the ages of 40 and 80 years old.Data analysis using Product Moment correalation technique showed r = 0,417 with p <0,01 pointing out that there is significant positive correlation between religiousity andsubjective well being. That result proved that hypothesis was accepted. Anotherconclusion of this study is religiousity and subjective well being of coronary heart patientsare at the medium category.